Validation of the analytical method using the energy dispersive X-ray fluorescence technique (EDXRF) for application in pharmaceutical sciences (Brazilian Journal of Radiation Sciences (BJRS), 2022)
The determination of impurities in raw materials intended for the production of pharmaceutical products is important to guarantee the quality of the final product, as well as to avoid damage to health. Metallic impurities can exhibit toxic effects even at low concentrations and so permissible levels are defined by the regulatory agencies and pharmacopeias. However, few methods are presented in official compendia in Brazil. In this sense, fast, sensitive, and precise techniques such as the energy dispersive X-ray fluorescence technique (EDXRF) must be evaluated for the analysis of metals in materials for pharmaceutical use. This way, therefore, there is the need to investigate the presence of contaminants and their concentration levels. The major goal of this research work was to validate a method for using the Energy Dispersive X-Ray Fluorescence (EDXRF) technique to identify and quantify the chemical composition of raw materials and pharmaceutical products. The methodology used was based on the selection of a microcrystalline cellulose matrix, which was spiked with two classes of contaminant elements, Class 1 (Cd, Pb, As, Hg) and Class 2A (Co, V, Ni) as defined by ICH guideline Q3D. The qualitative and quantitative analyses were carried out using the EDXRF technique, which proved to be quite effective and met all the validation parameters required in the mandatory official compendia (Resolution of the Collegiate Board (RDC) of Brazilian Health Regulatory Agency (Anvisa) nº 166, July 24, 2017), such as selectivity, linearity, precision, detection limit, quantification limit and robustness. This study showed that EDXRF can be used as a technique for detection and quantification of elemental impurities belonging to Class 1 and Class 2A.